The epidemiology of the viral hepatitis in Brazil: A scoping review - Cesar Augusto Inoue; Thais Sena de Paula Domingues; Maria Cecilia Araripe Sucupira; Roberta Sitnik; Caroline Thomaz Panico; Denize Ornelas Pereira Salvador de Oliveira; Isis Aleixo Barone Esquiçati; Ketti Gleyzer de Oliveira; Nathalia Villa dos Santos; Peter James Robinson; Raquel Queiroz de Araujo; Roberta dos Santos Pereira; et al. (PLoS ONE, 2026)
Background Brazil has advanced toward eliminating viral hepatitis by 2030 through broad prevention, diagnosis, and treatment policies. Yet substantial gaps persist across the care continuum, especially in vulnerable populations and underserved regions. This scoping review synthesizes nationwide epidemiologic patterns and identifies knowledge gaps to inform policy. Methods We conducted a PRISMA‑guided scoping review on seven databases (2013–2024) for Portuguese/Spanish/English observational studies or systematic reviews with post‑2010 data, extracting epidemiological patterns by viral hepatitis type and population group. Results Across 200 included studies, the combined sample encompassed more than 14.5 million individuals. Hepatitis B was the most studied, followed by hepatitis C. Hepatitis A seroprevalence in general population ranged from 33.3–67.8%. In vulnerable populations, highest seroprevalence was among incarcerated populations (88.1%), followed by immigrants (87.4%) and transgender individuals (75.6%). Hepatitis B presented HBsAg prevalence ranging from 0–7.5% in the general population, with the highest rates in an endemic Amazon region. Hepatitis C seroprevalence varied from 0.04–2.2% in the general population, with higher rates among people who use drugs (36.9%). Hepatitis D was predominantly reported in the Amazon region, with prevalence ranging from 0–23.9%. For hepatitis E, prevalence in the general population ranged from 0.9–59.4%, with the highest value in the South region. Conclusions Viral hepatitis in Brazil shows heterogeneous epidemiologic patterns across regions and populations, alongside unequal research output. The predominance of small, cross‑sectional studies and their limited integration with social determinants of health highlight the need for future research employing methodologies that address the gaps identified in this review. The resulting evidence map can guide policies aligned with national elimination goals.